The Gunsmith: The Lady Doctor's Alibi - Book 339 - Roberts, J. R., 1951- (New York : Jove Books, 2010)
When Veracruzs male doctor is killed, fingers point toward the towns female sawbones, Doctor Sugarman, who stands to inherit his clientele. But the killer could have been the dead doctors cheating wife. Either way, the Gunsmith will have justice served.
Keywords: Adams, Clint (Fictitious character) -- Fiction; Women physicians -- Fiction; Murder -- Investigation; Fiction; Western fiction